A Feasibility Study on Nano-Particle Properties for Signal Generation at NaI(Tl) Scintillation Detectors - Siamak Hooshmand Koochi; Ahmad Esmaili Torshabi (Frontiers in Biomedical Technologies)
Purpose: Scintillators have become a prevalent method for detecting ionizing radiation due to their ability to produce optical photons that serve as the basis for the final signal representing the physical properties of the incident beam. This signal is generated using interface hardware such as photon multipliers or photodiodes, in conjunction with the scintillator body. A feasibility study was undertaken to investigate a new interface and detector body based on nano-technology and nano-particle materials, which could potentially eliminate the need for the current photon multipliers.